Exploring the relationship between competitive anxiety and archery performance: evidence from Malaysian athletes / Muhammad Farhan Hakim Rhyme and Rozita Abdul Latif - Rhyme, Muhammad Farhan Hakim; Abdul Latif, Rozita (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Competitive anxiety significantly impacts athletic performance, particularly in precision sports like archery [1]. This study examines competitive anxiety types among SUKMA and AUG archers, identifies their performance outcomes in various event contexts, and explores the relationship between anxiety levels and performance outcomes [2]. By understanding these dynamics, this research provides insights to optimize mental preparation strategies, aiming to enhance competitive performance among archers [3]. Competitive anxiety was assessed using the Sport Anxiety Scale-2 (SAS-2), measuring worry, concentration disruption, and somatic anxiety on a four-point Likert scale. Performance was evaluated during scoring events, with archers shooting 72 arrows for a maximum score of 720 points. The study sampled 207 athletes (SUKMA and AUG) from 14 Malaysian states, employing purposive sampling.